### Home > A2C > Chapter 2 > Lesson 2.1.7 > Problem 2-102

2-102.

For the function

*g*(*x*) =*x*^{3}+*x*^{2}− 6*x*, find the value of each expression below. Homework Help ✎*g*(1)*g*(−1)*g*(−2)*g*(10)Find at least one value of

*x*for which*g*(*x*) = 0.If

*f*(*x*) =*x*^{2}−*x*+ 3, find*g*(*x*) −*f*(*x*).

Substitute 1 for *x* in the given equation and then evaluate.

8

Let *g*(*x*) = 0 in the original equation and then solve for *x*.

*x* = −3, 0, 2

6

*g*(*x*) − *f*(*x*) = (*x*^{3} + *x*^{2} − 6*x*) − (*x*^{2} − *x* + 3)